PECULIARITIES OF REPRODUCING EXPRESSIVE MEANS IN POLITICAL SPEECHES TRASLATION - Baranova, Baranova Svitlana; Nazarenko, Olena; Makarenko, Vlada (Philological Treatises, 2023)
The translation of political speeches is crucial in today's globalized world, where leaders communicate with audiences of different languages and cultures. Reproducing expressive devices is particularly important as it significantly affects the understanding and interpretation of the message. This study aims to identify the peculiarities of reproducing expressive means in political speeches translation, including metaphors, allegories, antitheses, and other rhetorical devices used by prominent politicians.The primary goal is to ensure that the translated speech accurately conveys the intended message and style of the speaker while adapting them to the cultural and linguistic context of the target audience. Materials and methods of research involved analyzing speeches of famous politicians in the source language, working with native speakers of the target language to ensure accuracy and cultural sensitivity and reviewing the translated speech for clarity, coherence, and persuasiveness.The study's results indicate that the translation of expressive means requires careful consideration of cultural, linguistic, and rhetorical contexts, and appropriate target language equivalents to maintain the integrity of the original message and style. The understanding of these nuances can enhance cross-cultural communication and foster global cooperation. In conclusion, the study highlights the importance of reproducing expressive means in political speeches translation to ensure clear, coherent, and persuasive communication across languages and cultures.